2011
DOI: 10.4269/ajtmh.2011.10-0002
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Meglumine Antimoniate in Acute Cutaneous Leishmaniasis: Children versus Adults

Abstract: Some studies showed that children have a lower response to systemic use of pentavalent antimoniate than adults. We aimed to evaluate the response rate to Glucantime therapy in children and compare it with adults. One hundred and twelve patients with acute cutaneous leishmaniais (ACL) were divided into two equal groups of adults (> 15 yrs) and children (≤ 15 yrs). They received meglumine antimoniate; 20 mg/kg/day for 20 days, their improvement rate was evaluated 20 and 45 days after treatment. Perprotocol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
0
22
0
2
Order By: Relevance
“…A number of other studies have yielded similar results. Layegh et al showed that systemic Glucantime® has a significantly lower efficacy in treating acute cutaneous leishmaniasis in children than in adults (22). In another study performed on L. viannia species, cutaneous treatment by systemic Glucantime® also had a clinically significant lower response in children when compared with the same regimen dosage and duration in adults (23).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have yielded similar results. Layegh et al showed that systemic Glucantime® has a significantly lower efficacy in treating acute cutaneous leishmaniasis in children than in adults (22). In another study performed on L. viannia species, cutaneous treatment by systemic Glucantime® also had a clinically significant lower response in children when compared with the same regimen dosage and duration in adults (23).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum daily dose of SbV for children under 12 years of age must not exceed 121.5mg (7.5ml), and treatment of children under 18 months is not recommended 39 . However, CL treatment with meglumine antimoniate is less effective in children than in adults [40][41][42] . The lower effi cacy may result from the pathogenicity of the parasite or the particular immune response of this age group 40,42 .…”
Section: Resultsmentioning
confidence: 99%
“…[5] Leishmaniasis is a diverse and complex disease. Each species can produce more than one clinical form of the disease and each form of the disease could be caused by multiple species.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…L. tropica is capable of surviving in a latent state in previously affected tissues and may have spread after the cutaneous lesion healed. [12] Since mucosal involvement due to old-world leishmaniasis is not frequent and the few reported cases concern immunocompromised patients, [5] we assessed our patient in this respect. He had no signs of immunodeficiency.…”
Section: Discussion Discussionmentioning
confidence: 99%